(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2011)
In this paper two spreading schemes and their detection methods were proposed and compared. The comparison depends on the performance of each scheme in Rayleigh flat fading channel. Space Time Spreading (STS) codes are used with Layered Space Time Codes(LST), with Vertical Bell Laboratories Space Time codes (V-BLAST) in particular. Also,Direct Sequence Code Division Multiple Access system (DS-CDMA) was used as a multi-user criterion. As a result of this spreading, a simple decoding algorithm was used. The simulation shows that STS-LST-DS-CDMA system with 3TX-3RX (3 transmitting antennas-3 receiving antennas) using all paths between transmitter and receiver was better than LST-DS-CDMA system by about 4dB in SNR at BER of 10-4. More detailed results are shown in Table 1. Also, the proposed scheme (may be partially) solves the problem of the code reuse.